Reverse Total Shoulder Arthroplasty for Geriatric Proximal Humerus Fracture Dislocation With Concomitant Nerve Injury. (7th June 2019) - Gasbarro, Gregory; Crasto, Jared A.; Rocha, Jorge; Henry, Sarah; Kano, Daiji; Tarkin, Ivan S.
Introduction: Preoperative axillary nerve palsy is a contraindication to reverse total shoulder arthroplasty (rTSA) due to the theoretical risk of higher dislocation rates and poor functional outcomes. Treatment of fracture-dislocations of the proximal humerus with rTSA is particularly challenging, as these injuries commonly present with concomitant neurologic and soft tissue injury. The aim of the current study was to determine the efficacy of rTSA for this fracture pattern in geriatric patients presenting with occult or profound neurologic injury. Methods: A retrospective case series of all shoulder arthroplasty procedures for proximal humerus fractures from February 2006 to February 2018 was performed. Inclusion criteria were patients aged greater than 65 years at the time of surgery, fracture-dislocations of the proximal humerus, and treatment with rTSA. Patients with preoperative nerve injuries were compared to patients without overt neurologic dysfunction. Forward elevation, Quick Disabilities of the Arm, Shoulder, and Hand (QuickDASH), Visual Analog Scale (VAS), and Subjective Shoulder Value (SSV) were obtained at final follow-up. Results: Forty-six rTSA for acute fracture were performed during the study period, 16 patients met the inclusion criteria and 5 (31%) presented with overt preoperative nerve injuries. At mean 3.1 years follow up, there were no postoperative complications including dislocations and final forward elevation was similar between study groups. Patients with overt nerve palsy had higher QuickDASH and VAS scores with lower SSV and self-rated satisfaction. Discussion: In the majority of patients with or without overt nerve injury, rTSA reliably restored overhead function and led to good or excellent patient-rated treatment outcomes. Overt nerve palsy did not lead to higher complication rates, including dislocation. Despite greater disability and less satisfaction, complete or partial nerve recovery can be expected in the majority of patients. Conclusion: Nerve injury following proximal humeral fracture dislocation may not be an absolute contraindication to rTSA.